(untitled) - Heileman, Gregory L. (New York, 1996)
The book provides a modern treatment of data structures and rigorous analyses of their corresponding algorithms. Implementation of these data structures is considered from the perspective of object-oriented programming, and is supported by detailed examples in C++
Keywords: Algorithms,Object-oriented databases